El Efecto Multiplicador de la Industria Minera Huasikury: Análisis del Impacto Indirecto en los Sectores Económicos Secundarios y Terciarios del Cantón Gualaquiza - Tibillin Suconota, Katherine Gissela (2024)
The impact of mining on society is of worldwide interest, as it can have both positive and negative effects on the economy and on people's well-being. In the Ecuadorian context, mining plays a significant role in the country's economic development, therefore, it is crucial to understand how mining affects the secondary and tertiary economic sectors, which are often less recognized, but equally important. Therefore, the objective of this research is to analyze the economic growth in the secondary and tertiary economic sectors of the Gualaquiza Canton, as a result of the influence of the Huasikury mining industry, and to identify the positive impact that mining has generated in these sectors. To carry out this study, a quantitative research was conducted with a descriptive approach, surveys were applied to companies active in the secondary and tertiary sectors, identified from the Internal Revenue Services September 2023 of the canton, a stratified sampling was used to ensure the representativeness of the sample. The results revealed the number of companies belonging to each sector and their perception of the influence of the mining company on their economic activity, an analysis of income, the number of employees that the surveyed companies currently have and how many they started with, as well as an analysis of the investment made in each sector. In conclusion, the influence of the mining company studied in the economic sectors is minimal; however, an active participation in the tertiary sector was identified, although of a reduced magnitude.